CNS RESPONSE IN A RABID BRAIN: A PATHOLOGICAL VIEW: Life Sciences-Pathology - PREETY SHARMA; SANJEEV KUMAR; V. K. SHARMA; AJAY KUMAR TEHLAN (International Journal of Life Science and Pharma Research, 2022)
Animal attacks constitute a huge medical and social problem ending in millions of injuries and thousands of deaths worldwide. Rabies is a dreadful infectious disease that has not been brought under control in many parts of the world even today. Rabies spread by domestic and wild animals particularly by a dog bite, and with the exception of Antarctica, rabies is present on all continents, taking a heavy toll on human lives. Many countries have the status of high-risk areas, but most of the countries around the globe gained the status of rabies free territories. This shows that rabies can be successfully ruled out from the high-risk areas by taking preventing measures and the situation may be better if we continue to untangle the mysterious pathophysiology of this disease. Understanding rabies invasion and its pathophysiology will further enhance the chances of improvement rabies related complications and mortality. Rabies is a prototypic infection of the nervous system in which the virus selectively infects neurons, using retrograde axonal transport to traffic in the nervous system. Neuroinvasiveness, neurotropism and neurovirulence are the major defining characteristics of this virus. The speed of virus uptake, the ability of the virus to spread efficiently from cell-to-cell and the rate of virus replication are the major factors that determine the pathogenicity of rabies virus. Present work tries to understand the different target areas of rabies virus in central nervous system.